Sinus node revisited in the era of electroanatomical mapping and catheter ablation. (18th January 2005) - Sánchez-Quintana, D; Cabrera, J A; Farré, J; Climent, V; Anderson, R H; Ho, S Y
Abstract : Objective: To study the architecture of the human sinus node to facilitate understanding of mapping and ablative procedures in its vicinity. Methods: The sinoatrial region was examined in 47 randomly selected adult human hearts by histological analysis and scanning electron microscopy. Results: The sinus node, crescent-like in shape, and 13.5 (2.5) mm long, was not insulated by a sheath of fibrous tissue. Its margins were irregular, with multiple radiations interdigitating with ordinary atrial myocardium. The distances from the node to endocardium and epicardium were variable. In 72% of the hearts, the whole nodal body was subepicardial and in 13 specimens (28%) the inner aspect of the nodal body was subendocardial. The nodal body cranial to the sinus nodal artery was more subendocardial than the remaining nodal portion, which was separated from the endocardium by the terminal crest. In 50% of hearts, the most caudal boundaries of the body of the node were at least 3.5 mm from the endocardium. When the terminal crest was > 7 mm thick (13 hearts, 28%), the tail was subepicardial or intramyocardial and at least 3 mm from the endocardium. Conclusions: The length of the node, the absence of an insulating sheath, the presence of nodal radiations, and caudal fragments offer a potential for multiple breakthroughs of the nodal wavefront. The very extensive location of the nodal tissue, the cooling effect of the nodal artery, and the interposing thick terminal crest caudal to this artery have implications for nodal ablation or modification with endocardial catheter techniques.